Structure and floristic diversity in permanent monitoring plots in forest ecosystems of Tuscany - Chiarucci, A; Dominicis, V De; Wilson, J B (Forest Ecology and Management, 2001)
The sampling method is described which is used for the sampling of plant species richness and cover in a monitoring project on forest ecosystems in Tuscany (named MONITO). Species richness is sampled through a nested plot design, with plot size ranging from 1 to 2500 m 2 , whereas species abundance is estimated in 100 m 2 plots. This sampling design is simple to install and to manage through time. Species diversity can be monitored not just at one single spatial scale but at many scales, and species±area relations can also be calculated. The analyses of the data that were collected produced the ®rst available data on species richness in relation to plot size for Tuscan forest ecosystems, indeed for any Italian forests. The Arrhenius Power function and the General Root models showed the best ®t. Turkey oak (Quercus cerris) woods located on slightly acidic soil were found to be the forest ecosystems with the highest species richness, con®rming and quantifying well-established ¯oristic- phytosociological knowledge. Habitat heterogeneity, measured by plot ¯oristic resemblance, showed how the Turkey oak woods were the most heterogeneous at the smaller spatial scales, but not at larger ones
Keywords: forest ecosystem monitoring; habitat-heterogeneity; Permanent plots; species; species diversity; species-area relations

Short-term changes of response indicators of ecosystem status in broadleaved forests in Tuscany (central Italy) - Ferretti, M; Bonini, I; Bussotti, F; Celesti, C; Cenni, E; Chiarucci, A; Cozzi, A; De Dominicis, V; Grossoni, P; Leonzio, C (WATER AIR AND SOIL POLLUTION, 1999)
The status of different response indicators of forest condition were measured and assessed between 1995 and 1997 at 6 Permanent Monitoring Plots (PMPs) in Tuscany (central Italy), where beech, holm oak and Turkey oak are the most frequent tree species. Foliage transparency, leaf damage and crown dieback have changed significantly over the monitoring period. Leaf area, length of the current year shoots, and total leaf area changed as well, but only for Turkey oak. Changes were consistent between and within the plots. Different indices of plant diversity showed marked changes, apparently linked to natural dynamics within individual ecosystems. These rapid and contrasting fluctuations in the various indicators of forest ecosystem make it difficult to derive a synthesis about the general condition of ecosystems and - especially - about the effects of air pollution.
Keywords: Biodiversity; crown condition; crown productivity; forest health; long-term monitoring; Permanent plots; response indicators